DIGITIZING LOCAL LANGUAGES THROUGH AUDIO: AN APPLICATION FOR TRANSLATING INDONESIAN INTO THE PAPUAN MEE TRIBE LANGUAGE - Usman Arfan; Margaretha Yanuar Douw (Penelitian dan Pengembangan Ilmu, 2025)
The preservation of local languages is a significant challenge in the face of globalization and the dominance of national languages. One practical effort that can be undertaken is the utilization of digital technology to document and disseminate indigenous languages. This study aims to develop a web-based application capable of translating text from Indonesian into the Mee language of Papua, complemented by audio features using native speaker recordings. The system was developed using the Waterfall model, starting from requirements analysis, system design, implementation, and testing. The use case diagram illustrates the interaction between users and the system, consisting of two main actors: general users and administrators. Users can input Indonesian words to receive translations in Mee, along with audio output. Administrators have the authority to manage vocabulary data, upload audio files, and synchronize text with the corresponding recordings. The user interface design emphasizes simplicity while reflecting the cultural values of Papua. System testing, performed using black-box methods, confirms that all functional features operate correctly. Evaluation results also indicate the system is user-friendly and holds great potential in supporting the digital preservation of the Mee language.